Epidemiological monitoring of cancer risk in cancer center workers - L. G. Solenova (Успехи молекулярной онкологии)
Based on the results of cancer monitoring in the staff of a large Cancer Center cancer risk research was performed using the method of nested “case–control” study within a cohort. The cohort comprised 7269 persons who were followed up through the cancer-register of the Cancer Center. Four hundred eighty-four (139 male and 345 female) cancer cases were revealed. For every case a control individual of the same sex and age was randomly selected from the staff who had no cancer as of January 1, 2019. A statistically insignificant increase in the overall cancer risk was observed in male operational staff (odds ratio (OR) being 1.14, 95 % confidence interval (CI) 0.64–2.05) and other doctorsclinicians (OR 1.36; 95 % CI 0.68–2.73). In a combined group of male clinicians and experimenters 4 cases of thyroid cancer were revealed and no members of this group were present in controls. An insignificantly increased risk of hemoblastoses, skin and brain cancer were also observed in this group. In the female stuff an insignificantly increased risk of all cancer sites combined was recorded in operational group (OR 1.28; 95 % CI 0.58–2.87) and nurses (OR 1.21; 95 % CI 0.85–1.72), as well as in the female stuff of experimental scientific units (OR 1.31; 95 % CI 0.90–1.92). An insignificant increase in breast cancer risk was observed in women clinicians and experimenters, exposed to the occupational factors. Female employees of experimental scientific units demonstrated a statistically significant increased risk of digestive organs cancer (OR 2.95; 95 % CI 1.14–7.67) and hemoblastoses (OR 5.71; 95 % CI 1.05–31.07). The results of the study demonstrate the need for epidemiological monitoring and data accumulation on cancer risk in different groups of medical workers.